Liver-Targeting Class I Selective Histone Deacetylase Inhibitors Potently Suppress Hepatocellular Tumor Growth as Standalone Agents - Tapadar, Subhasish (Cancers (Basel), 2020)
SIMPLE SUMMARY: Liver cancers are among the leading causes of global cancer deaths. The current therapy options for liver cancers, including hepatocellular carcinoma (HCC), which accounts for over 80% of all cases, have afforded limited benefit to patients with an advanced disease state. HCC results from genetic and epigenetic alterations, including gene-silencing chromatin histone hypoacetylation. The aim of this study was to investigate the potential utility of liver tissue-targeting HDAC inhibitors (HDACi) as a new class of anti-HCC agents. We showed that a class of macrolide-based HDACi, which are selective for sub-class I HDACs, preferentially accumulated in the liver tissue and robustly suppressed tumor growths in an orthotopic model of HCC. The liver tissue-selective accumulation property of these compounds gives them a unique advantage over most of the current HDACi, including those currently in clinical use. ABSTRACT: Dysfunctions in epigenetic regulation play critical roles in tumor development and progression. Histone deacetylases (HDACs) and histone acetyl transferase (HAT) are functionally opposing epigenetic regulators, which control the expression status of tumor suppressor genes. Upregulation of HDAC activities, which results in silencing of tumor suppressor genes and uncontrolled proliferation, predominates in malignant tumors. Inhibition of the deacetylase activity of HDACs is a clinically validated cancer therapy strategy. However, current HDAC inhibitors (HDACi) have elicited limited therapeutic benefit against solid tumors. Here, we disclosed a class of HDACi that are selective for sub-class I HDACs and preferentially accumulate within the normal liver tissue and orthotopically implanted liver tumors. We observed that these compounds possess exquisite on-target effects evidenced by their induction of dose-dependent histone H4 hyperacetylation without perturbation of tubulin acetylation status and G0/G1 cell cycle arrest. Representative compounds 2 and 3a are relatively non-toxic to mice and robustly suppressed tumor growths in an orthotopic model of HCC as standalone agents. Collectively, our results suggest that these compounds may have therapeutic advantage against HCC relative to the current systemic HDACi. This prospect merits further comprehensive preclinical investigations.